Revalidation of Enteromius alberti and presence of Enteromius cf. mimus (Cypriniformes: Cyprinidae) in the Lake Edward system, East Africa - Maetens, Heleen; Van Steenberge, Maarten; Snoeks, Jos; Decru, Eva (European Journal of Taxonomy, 2020)
A revision was done on the species of Enteromius Cope, 1867 (Cypriniformes: Cyprinidae) from the Lake Edward system with a smooth, flexible third unbranched dorsal fin ray without serrations. Specimens with these characteristics had previously been attributed to E. perince and E. stigmatopygus. A combination of a genetic (COI, mtDNA) and a morphometric approach was used. Based on the COI gene, we found two groups with a distance of 8.5%, though neither of the two corresponded to E. perince or E. stigmatopygus. One group revealed to be conspecific with E. alberti, previously a synonym of E. stigmatopygus, described from the Rutshuru River, May-Ya-Moto (DRC, Lake Edward system), and revalidated here. In addition, E. cercops, described from the Nzoia River (Kenya, Lake Victoria basin), is put in synonymy with E. alberti. The second group was most similar to E. mimus, but differed morphologically somewhat from the types of E. mimus. Therefore, specimens of this group were identified as E. cf. mimus. Morphologically, E. alberti can be separated from E. cf. mimus based on a higher number of lateral line scales and smaller values for interorbital width, pre-pelvic distance, body depth, maximum and minimum caudal peduncle depth, head width and head depth.